Observations that suggest a contribution of altered dermal papilla mitochondrial function to androgenetic alopecia - Chew, Elaine Guo Yan (2022)
Androgenetic alopecia (AGA) is a prevalent hair loss condition in males that develops due to the influence of androgens and genetic predisposition. With the aim of elucidating genes involved in AGA pathogenesis, we modelled AGA with three-dimensional culture of keratinocyte-surrounded dermal papilla (DP) cells. We co-cultured immortalised balding and non-balding human DP cells (DPCs) derived from male AGA patients with epidermal keratinocyte (NHEK) using multi-interfacial polyelectrolyte complexation technique. We observed up-regulated mitochondria-related gene expression in balding compared with non-balding DP aggregates which indicated altered mitochondria metabolism. Further observation of significantly reduced electron transport chain complex activity (complexes I, IV and V), ATP levels and ability to uptake metabolites for ATP generation demonstrated compromised mitochondria function in balding DPC. Balding DP was also found to be under significantly higher oxidative stress than non-balding DP. Our experiments suggest that application of antioxidants lowers oxidative stress levels and improves metabolite uptake in balding DPC. We postulate that the observed up-regulation of mitochondria-related genes in balding DP aggregates resulted from an over-compensatory effort to rescue decreased mitochondrial function in balding DP through the attempted production of new functional mitochondria. In all, our three-dimensional co-culturing revealed mitochondrial dysfunction in balding DPC, suggesting a metabolic component in the aetiology of AGA.